Motorization index, legal and illegal vehicles: the case of Cuauhtémoc City, Chihuahua - Yañez Orozco, Humberto; Bravo Peña, Luis Carlos (Acta Universitaria, 2022)
This article presents the results of an investigation on the motorization index in Ciudad Cuauhtémoc, a city located in Northern Mexico, which has abnormal vehicle supply conditions due to the illegal imports of cars. The data were generated by analyzing a sample of 1296 vehicles using a transect technique, that consists in a random selection of samples in a zone linearly; the application of the method was repeated twice with similar results. The results revealthe existence of 37 816 to 40 398 illegally circulating cars out of the 122 165 total cars in the city. The results obtained are contrasted with the motorization indexes offered by INEGI, which only includes cars in legal circulation.Additionally, a reflection is offered on the possible consequences of the current public spending policy, as well as the effect of this on people's decision-making when they do not have access to a legal vehicle.